TINDAKAN KEPERAWATAN NERS DAN TERAPI THOUGHT STOPPING MAMPU MENURUNKAN ANSIETAS DAN POSTPARTUM BLUES PADA IBU POSTPARTUM DENGAN BAYI PREMATUR - Sri Laela (Akademi Keperawatan Hermina Manggala Husada, 2022)
Postpartum mothers with premature infants at risk for postpartum blues and anxiety, it is due to the many problems faced by postpartum mothers with premature infants. The purpose of this study identified the influence of thought stopping therapy against postpartum blues and anxiety postpartum mothers with premature infants. The method used a quasi-experimental control group pretest-posttest design with consecutive sampling method. The sample in this study is postpartum mothers with premature infants who were treated in the Perinatology - Nicu were 62 respondents. The results showed differences in postpartum blues and anxiety levels postpartum mothers with premature infants significant (p-value = 0.000) between the groups thought stopping therapy with groups that receive nursing actions. Thought stopping therapy can reduce postpartum blues and anxiety levels for postpartum mothers with premature infants greater than the provision of nursing actions